Humanistic and Peace Values in John Lennon’s Solo Albums - Marvino Diaz Athalah; Hafiz Arfansyah; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the representation of humanistic and peace values in John Lennon’s solo albums through a qualitative descriptive approach focusing on lyrical analysis. Eight songs released between 1970 and 1980—Imagine, Give Peace a Chance, Happy Xmas (War Is Over), Mind Games, Love, Working Class Hero, Beautiful Boy, and Watching the Wheels—were selected for their consistent articulation of themes such as unity, compassion, equality, and critiques of social injustice. Guided by Marc Pilisuk’s peace theory, the analysis interprets Lennon’s lyrics as cultural texts that embody moral and philosophical ideals rather than mere political statements. Findings reveal that Lennon’s works function as artistic expressions and ethical reflections, encouraging audiences to envision a world free from conflict and grounded in empathy and solidarity. His songs bridge personal experiences with global concerns, offering meaningful contributions to literary studies and peace discourse. Ultimately, Lennon’s solo albums highlight the transformative role of music in promoting humanity, justice, and peaceful coexistence.